Detection of Mycobacterium avium subsp. paratuberculosis and other mycobacteria in retail milk and dairy products in Argentina - Cirone, Karina Mariela; Morsella, Claudia Graciela; Mendez, Laura Luján; Paolicchi, Fernando (Ediciones INTA, 2022)
Mycobacterium avium subsp. paratuberculosis (MAP) is the etiologic agent of paratuberculosis or Johne’s disease (JD), a chronic enteritis disease that affects cattle and other animal species and has been linked to Crohn’s disease, a chronic inflammatory bowel disease in humans. MAP could resist pasteurization conditions and has been isolated from retail milk in several countries. The aims were to identify MAP and other mycobacteria in retail milk and dairy products in Argentina and to assess the product quality through Mesophilic Total Aerobic Bacteria (TAB) count. Three hundred and eighty-four samples of retail milk were tested for 24 months. All samples were negative for mycobacteria growth. However, 1.56% of the samples were positive for MAP identification by IS900-PCR. The TAB count was higher than the limits established by the Alimentary Argentinian Code (AAC) in 4.95% of the samples. Mycobacteria other than MAP were not detected either by culture or PCR. The MAP positive PCR from retail milk samples would indicate that they could come from dairy farms with JD and suggests that pasteurized milk or dairy products are not significant sources of human exposure to MAP in Argentina. Some milk samples exceeded the limits established by the AAC for TAB counts, indicating that commercialized milk could be processed and stored incorrectly.